PENINGKATAN KEMAMPUAN KOMUNIKASI MATEMATIS SISWA MELALUI PEMBELAJARAN REFLEKTIF DI SMA - Eriska Pitriani; Rohana Rohana; Yunika Lestaria Ningsih (Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to examine the improvement of mathematical communication of students of SMA Negeri 1 Lawang Kidul through Reflective Learning. The method of this research is quasi-experiment with pretest and postes group design. Population in this research that is all class X MIA SMA Negeri 1 Lawang Kidul, taken sample of two classes that class X MIA A many as 25 students as experiment class that get reflective learning (PR) and class X MIA C as much 27 students as control class get conventional learning (PK). The instrument used in this study is a Mathematical Communication Skills (KKM) test in the form of essays that have been empirically validated. Data analysis using t test (Independent samples t test), by first test the normality and homogeneity. Based on the analysis of the data, the results obtained in this study that the improvement of mathematical communication skills of students of SMA Negeri 1 Lawang Kidul who get reflective learning better than those who get conventional learning. Keywords: Reflective Learning, Mathematical Communication Skill